RANCANG BANGUN DAN NILAI DASAR UNIVERSAL EKONOMI ISLAM - Sulistyowati (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
The main concern of Islamic economics is on how human effort to improve the welfare of material which will simultaneously increase their spiritual welfare. Because the spiritual must be present along with the target material, it needs the main support means, namely morality ekonomi.Fondasi Islamic economic actors consists of five universal values, among others, monotheism, in the design of the economic base of Islam, meaning the monotheistic god so true owner of the entire existing in the universe and the gods did not create anything in vain, and man was created to worship. Adil is defined as oppressing and oppressed, the fair is put things in place. The implication of this value is that economic agents are not allowed to pursue personal gain when it harms others or damaging nature. Nubuwwah the main qualities that should be followed generally by humans, in particular by economic actors and businesses as exemplified by the Prophet Muhammad by nature siddiq, trust, fathanah and sermons in running the business enterprise, the next caliphate In Islam, the government plays the role of small, but very important in the economy. Its main role is to ensure the economy to run in accordance with sharia, and to ensure that no violation of the rights of man, the latter is Ma’ad (result) The implications of this value in the economic life and business. motivate businesses to make a profit. Profit world and the hereafter profit thus the concept of profit gain legitimacy in Islam. Fifth universal value of the economic foundations of Islam or Islamic economic foundation, the basis for the inspiration to formulate theories and propositions of Islamic economics.